Kaylee Congdon: capstone - Congdon, Kaylee, artist (Colorado State University. Libraries, 2024)
The artist's statement: My name is Kaylee Congdon and I am a Graphic Designer. As a first-generation graduate of Colorado State University with a Bachelor's degree in Fine Art, specializing in Graphic Design and Painting, alongside a minor in Film Studies, my journey into creativity began long before my academic pursuits. With a love for movies, music, and the visual arts, I've been immersed in the world of artistic expression since I can remember. With a belief in the power of art to evoke emotion and connect, my mission as a graphic designer is clear: to make the world feel through my creations. Each project is an opportunity to weave together elements of storytelling, color theory, and design principles. I craft experiences that leave a lasting impression on viewers. I carry with me determination, using it in every aspect of my work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design